2009
DOI: 10.1021/ic8022387
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Fluorometric and Colorimetric Sensing of Phosphate Ions by a Fluorescent Dinuclear Zinc Complex

Abstract: A fluorescent dinuclear zinc complex (1) has been prepared by an easy "one pot" method in which the lysine-based Schiff base ligand is generated in situ. The compound is characterized in detail by various spectroscopic techniques and single-crystal X-ray diffraction. Crystal data: monoclinic, C2, a = 18.31(13) A, b = 8.45(7) A, c = 11.20(8) A, beta = 90.11(6) degrees, V = 1733.6(2) A(3). Z = 2, R1 = 0.0442, wR2 = 0.1068, Flack(x) parameter = 0.03(2). Compound 1 is highly fluorescent, in both the solution phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(84 citation statements)
references
References 38 publications
2
81
1
Order By: Relevance
“…There are several examples of water soluble Znsalens that were found to be monomeric species in aqueous solutions, 27,28,61 and thus the effect of water on the aggregation of ZnL 1 in water needs to be further discussed. Generally, water is a Lewis base and a coordinating solvent, and can compete with the intermolecular Zn···O interaction, and hence may prevent aggregation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several examples of water soluble Znsalens that were found to be monomeric species in aqueous solutions, 27,28,61 and thus the effect of water on the aggregation of ZnL 1 in water needs to be further discussed. Generally, water is a Lewis base and a coordinating solvent, and can compete with the intermolecular Zn···O interaction, and hence may prevent aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that anions such as phosphate 23,27,61 and Br – 25 are able to coordinate Zn and dissociate Znsalen aggregates, however, with much smaller binding constants than pyridine. 61,62 In this work, we chose PO 4 3– (PBS buffer), Br – ( n Bu 4 NBr) and HBSS buffer (containing various inorganic anions), which are relevant to biological studies.…”
Section: Resultsmentioning
confidence: 99%
“…In general, copper(II) ion is known as fluorescence quencher. Recently, it has also been observed in the literature that the fluorescence emission of DNA and other substrates have significantly been quenched due to the binding with copper(II) ions [60][61][62]. Therefore, theoretical calculations strongly suggest that the binding of DNA with complexes 1 and 2 occurs more possibly through the copper centers which have been further supported by the fluorescence titration experiments having the significant quenching effect.…”
Section: Theoretical Calculationsmentioning
confidence: 77%
“…By contrast, in our previous work we for the first time disclosed a distinct approach to target (Schiff base)-containing compound, where the in situ formation of Schiff base ligand is explored [19]. Further similar attempts are also achieved by Powell and Churchill [20,21]. However, the detailed experiment conditions are very different.…”
mentioning
confidence: 96%